Selective metallization on glass surface by laser direct writing combined with supersonic particle deposition. (January 2022) - Jo, Seunghwan; Akin, Semih; Park, Min Soo; Jun, Martin Byung-Guk
Abstract: Selective metallization on glass surface technique has lot of potential applications in optoelectronics. Particularly, ultra-fine copper lines provide better optical transparency, which may enable to meet the demands of novel optoelectronic devices. In this paper, we propose a new manufacturing procedure to overcome the limitations of the traditional process and to achieve narrower copper lines on the glass surface. We, first, irradiate the glass surface by the femtosecond laser for more precise ablation, and then deposit the silver nitrate particles onto the irradiated region by using a supersonic particle deposition system. Copper lines with a linewidth of 1 µm were achieved by means of this new procedure, which is, to best our knowledge, the narrowest linewidth ever reported so far using laser direct writing and the subsequent electroless copper plating. We also demonstrate a highly transparent heater (i.e., 97% optical transparency) as an application of the proposed manufacturing approach.